2011
DOI: 10.5402/2011/381615
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Behaviour and Springback Study of an Aluminium Alloy in Warm Forming Conditions

Abstract: This study deals with the mechanical behaviour and material modelling of an AA5754-O alloy at elevated temperature. Experimental shear tests were performed from room temperature up to 200• C, and the material behaviour has been identified with both shear and tensile tests, as a function of temperature. To analyse the influence of temperature during forming over springback, a split-ring test is used. Experimental results are obtained and compared to numerical simulations performed with the finite element in-hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 44 publications
1
15
1
3
Order By: Relevance
“…Figure 11 shows that punch speed also played a dominant role in springback; as punch speed was increased, springback angles θ A and θ B were significantly decreased for the hot die/ punch forming condition for T blank = 250°C. The punch speed investigated in this study was much faster than previous studies (≥75 mm/s compared with 0.5-1 mm/s) [12,17]. In the case of angle θ A , it was found that it decreased by 55.9 % from 7.9°at 75 mm/s to 3.5°at 300 mm/s.…”
Section: Springback Of U-shaped Test-piece Under Hot Stamping Conditionscontrasting
confidence: 39%
See 2 more Smart Citations
“…Figure 11 shows that punch speed also played a dominant role in springback; as punch speed was increased, springback angles θ A and θ B were significantly decreased for the hot die/ punch forming condition for T blank = 250°C. The punch speed investigated in this study was much faster than previous studies (≥75 mm/s compared with 0.5-1 mm/s) [12,17]. In the case of angle θ A , it was found that it decreased by 55.9 % from 7.9°at 75 mm/s to 3.5°at 300 mm/s.…”
Section: Springback Of U-shaped Test-piece Under Hot Stamping Conditionscontrasting
confidence: 39%
“…This technology has been studied for many years [4,12], and it was found that the formability of aluminium alloys can be enhanced considerably to a level equivalent to that of mild steel, with a moderate increase in the forming temperature to the range of 150-350°C. To enhance formability, warm forming processes are usually conducted under isothermal conditions and thus the forming tools are also heated up to a temperature ranging from 150 to 350°C.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sıcaklık artışının bir diğer avantajı ise şekillendirme sırasında deformasyondan kaynaklı kap duvarlarındaki gerilmeleri azaltmasıdır. Geri yaylanma sac metal şekillendirmedeki önemli kusurlardan biridir [17]. Bu gerilme durumu kaplarda geri yaylanmalara sebep olur.…”
Section: Gi̇ri̇ş (Introduction)unclassified
“…Kim H S and Koç M [16] found that the dimensional accuracy of springback could be improved by U-shape warm forming of AA 5754-O aluminum alloy under higher blank holder force (BHF), which could be interpreted as the uniform distribution of stress in the thickness direction when BHF was high. Grèze R and Laurent H [17,18] investigated the springback of AA5754-O aluminum alloy by a split-ring test in warm forming conditions. It was found that the springback amount decreased by 67% at 200°C compared with room temperature.…”
Section: Introductionmentioning
confidence: 99%